Audiology for the Neurosurgeon. Issue 4 (April 2023) - Kingsbury, Sarah E.; Bogle, Jamie M.; Weisskopf, Peter A.; Deep, Nicholas L.
Abstract : Many conditions that neurosurgeons manage are associated with audiologic symptoms. Unilateral hearing loss and tinnitus, poor suprathreshold speech understanding, and dizziness are hallmarks of retrocochlear lesions. Understanding the difference between air and bone conduction thresholds and the importance of speech discrimination helps differentiate types of hearing loss and their neurological importance. Acoustic reflex, otoacoustic emissions, and auditory brainstem response testing are objective measures used to determine function of the auditory structures. Accurate interpretation of these results can aid neurosurgeons in making differential diagnoses and determining surgical approaches. Cooperation among neurosurgeons, otolaryngologists, and audiologists ensures abnormal auditory symptoms are assessed correctly.